Sistem Dan Prosedur Pembayaran Retribusi Perizinan Usaha: Studi pada Kantor Pelayanan Terpadu Kabupaten Lumajang - Noviansyah Rizal (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2014)
Purpose of the establishment of the Office of Integrated Services Lumajang is to organize licensing service excellence (simple, clear, safe, transparent, efficient, economical, fair, and timely) through the door, because with this system will encourage the creation of a conducive business climate in order Lumajang economic empowerment. On his way Lumajang Integrated Services Office continues to monitor and evaluate the passage of the main tasks and functions. Fund the acquisition of the levy observations should be optimized by managing and improving systems and procedures of existing services. The purpose of this study is: 1. To analyze the system and the retribution business licensing procedures in the Office of Integrated Services Lumajang, 2. To analyze the internal control systems and procedures for payment of licensing fees in the Office of Integrated Services Lumajang, Sources of the data in this study is primary data and secondary data. The study was conducted by way of interview / interview, observation / observation and documentation. Data analysis method used is descriptive analysis method. Business licensing procedures retribution that make up the system at the Office of Integrated Services Lumajang are as follows: 1. Admission file, 2. Field, 3. Publishing SKRD, 4. Levy payment receipt (if received site visits). Internal control in order for the payment of licensing fees could be better, it is suggested for consideration: 1.a. To capture the local revenue, officers should continue to implement the existing systems and procedures, 1.b. To facilitate the applicant in order not to many times to come to the Office of Integrated Services Lumajang, a specified procedure informed / explained to the applicant; 2. Implementation of systems and procedures for the management of revenues from licensing fees, especially in the 1-hour time difference to the admissions office to make some sort of official report signed by the cashier and part acceptance BKP knowing or representing KPT Head, 3. Incompatibility educational background of employees with responsibilities tailored to their educational background.